Ahmet Yesevi’de Aşk Kavramı: Divan-ı Hikmet Üzerine Bir İnceleme - Gül, Halim (Journal of History Culture and Art Research, 2019)
As in Sufi thought, the concept of love is one of the fundamental dynamics of Ahmad Yasawi’s thought. According to Yasawi, it is only by love possible that the human being can communicate with his creator. Therefore, all creatures have innate love. Love, a mediator between man and his Lord, is a fire that burns everything except the beloved. If there was no love, there would not be any being. Thus, reason and logic alone never suffice to understand the existence. So, the nature of life is incomprehensible without love. The sense of love is a characteristic exclusive to human among the beings. Islam, the most appropriate religion for human nature, and Islamic society formed in the spiritual atmosphere of this religion have processed this divine and human sense especially through mysticism in accordance with the purpose of the creation of humankind, and transformed it into the driving force of Islamic civilization. Not found as a term but included as a concept in the Qur’an and Sunnah, love (ıshq) is in detail discussed in the Sufi works, and expressed by a great deal of symbols. According to the Sufi thought, the reason for the creation of the creatures is Allah’s desire to be known and the affection he has toward his creatures. Therefore, the creatures have risen to the level of existence owing to the affection between the Creator and the created. Due to the fact that love is a feeling exclusive to humankind, human being has become the caliph of Allah. The concept of love is of great importance in the Sufi thought, especially in Diwan al-Hikmah by Ahmad Yasawi.